2015
DOI: 10.1007/s11258-015-0532-2
|View full text |Cite
|
Sign up to set email alerts
|

Forest fragmentation in the Argentine Chaco: recruitment and population patterns of dominant tree species

Abstract: The forest in the Central Argentine Chaco has been dramatically fragmented and persists only as isolated patches in an agricultural matrix. In this study, we evaluated the effects of fragmentation on total density, recruitment, and size-class structure of its dominant tree species, a key issue, although little explored, for forest conservation in the region. We particularly analyzed the effects of fragment size and forest cover at landscape level on seven of the most important tree species of the forest. Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 47 publications
1
7
0
5
Order By: Relevance
“…Neither does our data support the idea that both of the studied timber species are truly shade-intolerant species, and therefore depend on direct sunlight to establish and grow. Our results are supported by a study carried out in another fragmented Chaco forest, where both A. quebracho-blanco and a congeneric species of S. lorentzii might also be capable of regenerating under the canopy of the forest (Torrella et al, 2015). Manipulative controlled studies might confirm the trends reported in this study and help advance our understanding regarding the causal relationship between natural regeneration and sunlight.…”
Section: Indirect Effects Of Logging Intensity On Timber Tree Regenerationsupporting
confidence: 87%
“…Neither does our data support the idea that both of the studied timber species are truly shade-intolerant species, and therefore depend on direct sunlight to establish and grow. Our results are supported by a study carried out in another fragmented Chaco forest, where both A. quebracho-blanco and a congeneric species of S. lorentzii might also be capable of regenerating under the canopy of the forest (Torrella et al, 2015). Manipulative controlled studies might confirm the trends reported in this study and help advance our understanding regarding the causal relationship between natural regeneration and sunlight.…”
Section: Indirect Effects Of Logging Intensity On Timber Tree Regenerationsupporting
confidence: 87%
“…Although large forest fragments provide better habitats for many forest species, the small ones are also important to be preserved particularly in cases when they function as stepping stones for connecting large forest remnants (Piquer-Rodríguez et al 2015). For instance, Torrella et al (2015) showed that small fragments in the Three Quebrachos Forest of the Central Chaco presented the same density and size-class structure than the larger ones in the dominant trees Schinopsis balansae , Aspidosperma quebrachoblanco , Prosopis kuntzei among others, but these forest remnants are strongly threatened by agriculture expansion. In this context, the usage of non-timber forest resources, such as the meliponiculture, would allow the gene flow by pollen dispersal among isolated individuals and patches and therefore enhance the resistance to the negative effects of the fragmentation.…”
Section: 5 R E C O M M E N D a T I O N S O N F O R E S T Management For Native Pollinator Conservationmentioning
confidence: 99%
“…The overgrazing, logging, deforestation and fires are the most common disturbances of the Argentine Chaco forests [10][11][12]. Fire is used from pre-Colombian times to promote new growth of grasses and to control shrubby encroachment in Chaco savannas [13].…”
Section: Introduction mentioning
confidence: 99%